“I have no idea how I will get a stipend”: the impact of COVID-19 on graduate students’ financial security - Zhen, Fubiao; Graves-Boswell, Taylor; Rugh, Michael S.; Clough, Jake M. (Frontiers in Education, 2024)
In this study, we investigated graduate students' financial security during the COVID-19 pandemic. In the Spring 2022 semester, the continued changes brought on by the precautionary measures implemented presented difficulties for both faculty and graduates. In this mixed methods study, we surveyed graduate students (N = 258) at a public research university to explore the pandemic's effects on their financial security. Through the sign test analyses, we found a significant decrease in graduate students' financial security scores during the pandemic, and particular groups of students were more susceptible to decreased financial security. The thematic analysis further explored the financial security decrease and identified inflation and economic downturns, and the suspension of work or financial support as two main challenges graduate students confronted during the pandemic. Both quantitative and qualitative findings reflected the financial stress and hardship confronted by graduate students during the pandemic. It was implied that extra financial support and consultation should be provided to students with meager stipends or student loans. The results further informed the academic community to foster the culture of care inside academia, by addressing graduate students' financial concerns properly in the post-pandemic period.